Dermatúnel: Modelo de ambiente interativo de aprendizagem em dermatologia - Paixão, Maurício Pedreira; Miot, Hélio Amante [UNESP]; Filho, Jayme de Oliveira; Wen, Chao Lung (FapUNIFESP (SciELO), 2009)
The Interactive Learning Environment (ILE) is an educational model that integrates features of 3D computer graphics and contextualization, in order to transmit a quantum of knowledge (islands of knowledge), in a precise and agile way, to people who do not know the subject. It is a model that uses multimedia resources supported by a contextualized environment to motivate the participants in the retention of knowledge. In this first release, eight relevant subjects in dermatology were addressed and implemented in the 62nd Brazilian Congress of Dermatology. The model was called Dermatúnel. In a period of four days, 3295 people visited it. The results showed that the participants were highly satisfied. The model has a great potential as an educational tool for medical training and guidance to the general public with the purpose of disease prevention.
Dermatúnel: A model of interactive learning environment in dermatology
Keywords: Audio-visual aids; Distance education; Health education; Multimedia; Telemedicine